VUV stimulated solid-phase reactions on the surface on Ni nano-layers on Si substrate - Mikhailov, I.F.; Malykhin, S.V.; Borisova, S.S.; Fomina, L.P. (Functional Materials, 2006)
Using X-ray reflectometry method, the kinektics of solid state reactions at the surface of layered thin film nickel/Sisub system (effective nickel thickness 15 and 45 nm) under VUV irradiation of 8≤hv≤1.8 eV energy was studied. Nickel and nickel oxide layers have shown no changes both in thickness and sesity. As a result of VUV stimulated silicon diffusion from the substrate and of its reaction with nitrogen, a new layer of silicon nitride with of (3.2...3.4) g*cm⁻³ desity in formed at the nickel film surface. The silicon nitride formation reaction, where nickel acts as a catalyst, is of zero order typical of radiation-(photo)-chemical processes and stops at the layer thickness about 1.5 nm. After aging in air, the surface layer density decreases down to 2.3 g*cm⁻³ and thickness increases to about 25 nm due to oxidation. Repeated cycles of irradiation and oxidation result in degradation of the film-substrate system due to breakink the film adhesion